2019
DOI: 10.1259/bjr.20180978
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative evaluation of computed and voxelwise computed diffusion-weighted imaging in breast cancer

Abstract: Objectives: To assess the value of computed diffusion-weighted imaging (cDWI) and voxelwise computed diffusion-weighted imaging (vcDWI) in breast cancer. Methods: This retrospective study involved 130 patients (age range, 25–70 years; mean age ± standard deviation, 48.6 ± 10.5 years) with 130 malignant lesions, who underwent MRI examinations, including a DWI sequence, prior to needle biopsy or surgery. cDWIs with higher b-values of 1500, 2000, 2500, 3000, 3500, and 4000 s/mm2, and vcDWI were generated from mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…Traditional nursing applies the same intervention measures to all patients, fails to consider the different disease states and nursing needs of different patients, and is very limited in terms of its clinical treatment efficacy. Conversely, personalized nursing with a quantitative evaluation of the initial severity of the disease with scientific scales, implements differentiated resource allocations and nursing intensity for patients with different symptoms and severity levels, so as to meet the needs of different patients, and improve nursing efficiency (28)(29)(30)(31).…”
Section: Discussionmentioning
confidence: 99%
“…Traditional nursing applies the same intervention measures to all patients, fails to consider the different disease states and nursing needs of different patients, and is very limited in terms of its clinical treatment efficacy. Conversely, personalized nursing with a quantitative evaluation of the initial severity of the disease with scientific scales, implements differentiated resource allocations and nursing intensity for patients with different symptoms and severity levels, so as to meet the needs of different patients, and improve nursing efficiency (28)(29)(30)(31).…”
Section: Discussionmentioning
confidence: 99%
“…For example, in high-resolution breast DWI, 29 the signal-to-noise ratio generally decreases and thus lower b-values might be optimal for lesion detection. An important approach in such a setting might be to acquire only data up to, for example, 1000 or 1500 s/mm 2 and compute the high b-value images 22,30 . Other factors such as different fat saturation approaches and dependence on scanner technology may also be of importance with respect to the generalizability of this optimal b-value finding 31 …”
Section: Discussionmentioning
confidence: 99%
“…An important approach in such a setting might be to acquire only data up to, for example, 1000 or 1500 s/mm 2 and compute the high b-value images. 22,30 Other factors such as different fat saturation approaches and dependence on scanner technology may also be of importance with respect to the generalizability of this optimal b-value finding. 31 In this study, 1 breast cancer recurrence was overlooked without CE in a woman after breast-conserving therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the studies have almost exclusively focused on the visibility of breast cancer [20,22,[33][34][35][36]; therefore, there is limited information on the conspicuity of benign breast lesions at high or synthetic b-values. While Chen et al [37] found no significant differences in conspicuity grades using b-values of 600, 800, and 1000 s/mm 2 , our results point to a difference in conspicuity.…”
Section: Discussionmentioning
confidence: 99%
“…Although synthetic b-values over 1000 s/mm 2 have demonstrated an improvement in tumor visualization and image quality [ 19 , 20 , 22 , 34 , 35 , 40 43 ], DCE-MRI outperforms DWI for breast cancer visualization and detection with a higher sensitivity across all readers. This is in accordance with the current literature: DCE-MRI outperforms unenhanced MRI with or without supportive sequences for cancer visualization [ 9 , 16 ].…”
Section: Discussionmentioning
confidence: 99%